Narrowing the Genetic Causes of Language Dysfunction in the 1q21.1 Microduplication Syndrome - Benítez-Burraco, Antonio; Barcos-Martínez, Montserrat; Espejo-Portero, Isabel; Fernández-Urquiza, Maite; Torres-Ruiz, Raúl; Rodríguez-Perales, Sandra; Jiménez-Romero, Ma Salud (Frontiers in Pediatrics, 2018)
The chromosome 1q21.1 duplication syndrome (OMIM# 612475) is characterized by head anomalies, mild facial dysmorphisms, and cognitive problems, including autistic features, mental retardation, developmental delay, and learning disabilities. Speech and language development are sometimes impaired, but no detailed characterization of language problems in this condition has been provided to date. We report in detail on the cognitive and language phenotype of a child who presents with a duplication in 1q21.1 (arr[hg19] 1q21.1q21.2(145,764,455-147,824,207)x3), and who exhibits cognitive delay and behavioral disturbances. Language is significantly perturbed, being the expressive domain the most impaired area (with significant dysphemic features in absence of pure motor speech deficits), although language comprehension and use (pragmatics) are also affected. Among the genes found duplicated in the child, CDH1L is upregulated in the blood of the proband. ROBO1, a candidate for dyslexia, is also highly upregulated, whereas, TLE3, a target of FOXP2, is significantly downregulated. These changes might explain language, and particularly speech dysfunction in the proband.